2017
DOI: 10.1101/172445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Domain-General and Domain-Specific Patterns of Activity Supporting Metacognition in Human Prefrontal Cortex

Abstract: Metacognition is the capacity to evaluate the success of one's own cognitive processes in various domains, e.g. memory and perception. It remains controversial whether metacognition relies on a domain-general resource that is applied to different tasks, or whether self-evaluative processes are domain-specific. Here we directly investigated this issue by examining the neural substrates engaged when metacognitive judgments were made during perceptual and memory tasks matched for stimulus and performance characte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(121 citation statements)
references
References 71 publications
29
92
0
Order By: Relevance
“…The newly involving fMRI activities during the redecision phase in comparison to those during the first decision‐making phase are not necessarily related to metacognition, could be generally associated with the second decision‐making. However, the fMRI activities in the MCN predominately occurring during the redecision phase were subject to the decision uncertainty levels on the preceding decisions, similar to the findings in the previous studies (Fleming et al, ; Morales et al, ; Qiu et al, ; Wan et al, ). Specifically, we here found that metacognitive abilities of decision uncertainty monitoring were lower, and the strengths of fMRI activities in the MCN, especially in dACC, were consistently much more reduced in SZ than HC.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The newly involving fMRI activities during the redecision phase in comparison to those during the first decision‐making phase are not necessarily related to metacognition, could be generally associated with the second decision‐making. However, the fMRI activities in the MCN predominately occurring during the redecision phase were subject to the decision uncertainty levels on the preceding decisions, similar to the findings in the previous studies (Fleming et al, ; Morales et al, ; Qiu et al, ; Wan et al, ). Specifically, we here found that metacognitive abilities of decision uncertainty monitoring were lower, and the strengths of fMRI activities in the MCN, especially in dACC, were consistently much more reduced in SZ than HC.…”
Section: Discussionsupporting
confidence: 85%
“…The trial‐by‐trial neural activity (n‐ AUC ) quantitatively characterized the individual metacognitive ability of decision uncertainty monitoring (b‐ AUC ), underlying the metacognitive deficit in SZ. As the MCN is commonly associated with metacognition accompanying a variety of decision‐making tasks (Fleming et al, ; Morales et al, ; Qiu et al, ; Wan et al, ), the association of hypo‐activity in the MCN with the metacognitive deficit in SZ could be general. The hypo‐activity in the MCN was consistent with the replicated findings of structural and functional abnormalities in this network in SZ (Brugger & Howes, ; Carter et al, ; Goodkind et al, ; Kerns et al, ; Pettersson‐Yeo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the data of Babayan et al. () concur with the finding that perceptual and memory‐specific metacognitive representations coexist with generic confidence signals (Morales, Lau, & Fleming, ). In fact, activity in the anterior prefrontal cortex was reported to predict levels of confidence in a domain‐specific fashion, whereas domain‐general signals predicted confidence and accuracy in frontal and parietal midline areas.…”
supporting
confidence: 62%